2013
DOI: 10.1038/ismej.2013.159
|View full text |Cite
|
Sign up to set email alerts
|

Making a living while starving in the dark: metagenomic insights into the energy dynamics of a carbonate cave

Abstract: Carbonate caves represent subterranean ecosystems that are largely devoid of phototrophic primary production. In semiarid and arid regions, allochthonous organic carbon inputs entering caves with vadose-zone drip water are minimal, creating highly oligotrophic conditions; however, past research indicates that carbonate speleothem surfaces in these caves support diverse, predominantly heterotrophic prokaryotic communities. The current study applied a metagenomic approach to elucidate the community structure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
121
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(134 citation statements)
references
References 63 publications
6
121
1
1
Order By: Relevance
“…Feldhake observed that the organic matter and microbial biomass content were lower in sediments from North American caves compared to forest soils. Moreover, recent research using molecular methods showed higher values for microbial biomass on the surface than inside Kartchner Caverns, USA (Ortiz et al, 2013;Ortiz et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Feldhake observed that the organic matter and microbial biomass content were lower in sediments from North American caves compared to forest soils. Moreover, recent research using molecular methods showed higher values for microbial biomass on the surface than inside Kartchner Caverns, USA (Ortiz et al, 2013;Ortiz et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This analysis showed that the RSF microbial community has relatively high proportions of chaperones and genes involved in post-translational modification and protein turnover (category O) as well as coenzyme transport and metabolism (H). These two categories have been detected to be abundant in oligotrophic ecosystems in comparison with higher nutrient availability ecosystems (Ortiz et al, 2013). The abundance of chaperones may help bacteria to deal with low nutrient availability and have been related to environmental stress tolerance (Storz and Hengge, 2011).…”
Section: Metagenomic Assembly and Taxonomymentioning
confidence: 99%
“…Caves are one of the habitable extreme habitats, and microorganisms have been determined in these ecosystems based on independent culture techniques in late 1990s such as in Nullarbor Cave, Australia (Holmes et al, 2001); Wind Cave, United States (Chelius and Moore, 2004); Niu Cave, China (Zhou et al, 2007); Altamira Cave, Italy (Portillo et al, 2009); Kartcher Caverns, United States (Ortiz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%